PENERAPAN METODE GUIDED INQUIRY TEACHING DENGAN MEMANFAATKAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII MIPA 8 SMAN 7 DENPASAR TAHUN PELAJARAN 2021/2022 - Desak Putu Kartiwi (Widyadari, 2023)
Students still experience difficulties in learning mathematics at school, so teachers need to innovate in using learning models to increase students' learning motivation. This research aims to determine the response and mathematics learning outcomes of class XII MIPA 8 students at SMAN 7 Denpasar after implementing the guided inquiry teaching method using mathematics learning media in statistics. This type of research is classroom action research (PTK). Action research is designed using two cycles and each cycle consists of four stages, namely: planning, implementation, observation and reflection. The research subjects were students of class The results of the research show (1) There is a positive response from students to the application of the guided inquiry teaching method by utilizing learning media in mathematics subjects in statistics material, (2) The guided inquiry teaching learning method by utilizing learning media can improve the mathematics learning outcomes of class XII MIPA 8 students SMAN 7 Denpasar 2021/2022 academic year. This can be seen from the learning results in the pre-cycle of 68.0, the first cycle was 74.0 and in the second cycle it was 78.125. So the conclusion is that applying the guided inquiry teaching method by utilizing learning media can improve the mathematics learning outcomes of class XII MIPA 8 students at SMAN 7 Denpasar for the 2021/2022 academic year.